Time trends in educational inequalities in cáncer mortality in Colombia, 1998-2012 (2016)
ABSTRACT: Objectives: To evaluate trends in premature cancer mortality in Colombia by educational level in three periods: 1998–2002 with low healthcare insurance coverage, 2003–2007 with rapidly increasing coverage and finally 2008–2012 with almost universal coverage (2008–2012). Setting: Colombian population-based, national secondary mortality data. Participants: We included all (n=188 091) cancer deaths occurring in the age group 20–64 years between 1998 and 2012, excluding only cases with low levels of quality of registration (n=2902, 1.5%). Primary and secondary outcome measures: In this descriptive study, we linked mortality data of ages 20–64 years to census data to obtain age-standardised cancer mortality rates by educational level. Using Poisson regression, we modelled premature mortality by educational level estimating rate ratios (RR), relative index of inequality (RII) and the Slope Index of Inequality (SII). Results: Relative measures showed increased risks of dying among the lower educated compared to the highest educated; this tendency was stronger in women (RRprimary 1.49; RRsecondary 1.22, both p<0.0001) than in men (RRprimary 1.35; RRsecondary 1.11, both p<0.0001). In absolute terms (SII), cancer caused a difference per 100 000 deaths between the highest and lowest educated of 20.5 in males and 28.5 in females. RII was significantly higher among women and the younger age categories. RII decreased between the first and second periods; afterwards (2008–2012), it increased significantly back to their previous levels. Among women, no significant increases or declines in cancer mortality over time were observed in recent periods in the lowest educated group, whereas strong recent declines were observed in those with secondary education or higher. Conclusions: Educational inequalities in cancer mortality in Colombia are increasing in absolute and relative terms, and are concentrated in young age categories. This trend was not curbed by increases in healthcare insurance coverage. Policymakers should focus on improving equal access to prevention, early detection, diagnostic and treatment facilities